Hereditary nonpolyposis colorectal cancer : factors contributing to adherence and non-adherence to surveillance for mutation carriers in rural areas of the Northern and Western Cape Brenda Julie Kruger. - Kruger, Brenda Julie (Division of Human Genetics, 2014)
Includes bibliographical references.